The Impact of Brand on Purchasing Decisions - Purwo Saputro, Edy; Probowati Setyaningrum, Dewi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
Many factors influence purchasing decisions as they relate to several aspects. It becomes more complex when the choice is diverse and prices vary, including the influencing factors that provide freedom of choice. Brand is the concept of consumers and affects consumers’ decision-making. Therefore, brand image and brand trust of consumers are linked to each other. Thus, brand image will affect brand trust of consumers. In addition, the brand also indirectly influences purchasing decisions due to the increasing number of products. To that end, this research’s problem is whether the brand influences purchasing decisions. This research method employed regression analysis involving samples of 100 students from Faculty of Economics and Business, Universitas Muhammadiyah Surakarta representing the millennial generation. The results showcased that brand image did not affect purchasing decisions, but brand trust did. Further, limitations and suggestions are presented for theoretical deepening and further research.